Power optimisation control of a guide-vanes integrated exhaust air turbine generator based on Vienna rectifier / Yip Sook Yee - Yip, Sook Yee (2018)
Exhaust air recovery system is a concept recently introduced to generate electrical power from cooling towers. It is an onsite energy generating system that consists of a vertical axis wind turbine (VAWT) connected to a permanent magnet synchronous generator (PMSG) and its power electronics converter. This system was designed to be retrofitted above exhaust air outlets of cooling towers to harness the discharged wind. While preliminary studies confirmed the feasibility of the concept, power optimization of the exhaust air recovery system is yet to be attempted. In this project, power optimization of the wind energy generated from the exhaust air recovery system was investigated based on both mechanical and electrical approaches. In this work, mechanical improvement was made by mounting guide-vanes between the exhaust air outlet and VAWT, with the purpose of augmenting wind power generation. Guide-vanes also help to divide the wind into several channels of airflow, whereby if they set at the correct angle, it would result in the induced wind being more uniform and better directed towards the optimized angle of attack of the wind turbine. By analyzing the discharge air profile of the exhaust air outlet, the optimized positions and angles of the guide-vanes were obtained. Experimental results based on a lab-scale turbine and the guide-vane system were validated with double multiple stream tube theory (DMST). On the electrical side, power optimization was made possible via efficient control of the PMSG and its power electronics converter. The Vienna rectifier was proposed to be used as the power electronics converter as a trade-off between cost and performance. Firstly, direct torque control (DTC) based on Vienna rectifier was investigated. An improved look-up table (LUT) was proposed to improve the overall control accuracy of the existing DTC in order to reduce the generated torque and stator flux ripples. The improvement was performed by increasing the comparing conditions of the torque comparator with more accurate selection of switching vectors. Meanwhile, computation delay compensation was also considered for digital implementation of the DTC. One drawback of the LUT-DTC is that the switching vector selection is done on an off-line basis, which is not optimized for all operating conditions. To further improve the effectiveness of the control method, a finite-set model predictive direct torque controller (MPDTC) was developed. To mitigate the well-known high computation burden problem of the MPC, a LUT was proposed to reduce the number of candidate switching vectors based on DC-link voltage errors. Simulation and experimental results confirmed the effectiveness of the proposed hybrid LUT-MPDTC method in regulating the torque and flux of the machine while maintaining a balanced DC-link. A maximum power point tracker was used on top of the developed MPDTC strategy to optimize the power extracted from the wind turbine. A lab-scale wind turbine emulator was developed using an induction motor that was controlled using field-oriented control. Electrical tests were conducted with the developed turbine emulator to verify the performance of the overall power optimization mechanism using the electrical approaches.